Template‐Directed Growth of Bimetallic Prussian Blue‐Analogue Nanosheet Arrays and Their Derived Porous Metal Oxides for Oxygen Evolution Reaction - Cao, Li‐Ming; Hu, Yu‐Wen; Zhong, Di‐Chang; Lu, Tong‐Bu (ChemSusChem, 2018)
Coordination polymers (CPs) are ideal precursors for synthesizing porous catalysts. However, the direct thermolysis of CPs is prone to generate agglomerates, greatly reducing the electrical conductivity and active sites of their derived catalysts. The construction of well‐ordered CP nanostructures is a promising strategy for alleviating the above issue, but it remains challenging. Here, a facile chemical etching approach is developed for the fabrication of well‐aligned three‐dimensional (3D) bimetallic Prussian blue‐analogue nanosheet arrays. Impressively, the derived porous metal oxide (Fe–NiO) acts as a remarkable oxygen evolution reaction (OER) catalyst, which merely requires overpotentials as low as 218 and 270 mV to achieve 10 and 100 mA cm−2 in 1.0 m KOH aqueous solution, respectively. The excellent electrocatalytic performance of Fe–NiO is ascribed to the 3D porous nanosheet array architecture, which endows the bimetallic catalyst with abundant electrocatalytic active sites, enhanced surface permeability, and high electronic conductivity. It is expected that the proposed strategy can pave a new way for fabricating highly efficient electrocatalysts for energy storage and conversion. A piece of art: Well‐ordered 3D bimetallic Prussian blue analogue nanosheet arrays are fabricated by etching Ni(OH)2 nanosheet arrays with potassium ferricyanide. The derived porous electrocatalyst exhibits excellent electrochemical activity and stability for the oxygen evolution reaction with overpotentials as low as 218 and 270 mV to achieve 10 and 100 mA cm−2 in 1.0 m KOH solution, respectively.